The Effect of Strategic Leadership on Performance Mediated by Organizational Ambidexterity in Batik SMES In Yogyakarta City - Adibah, Adelia Farah; Abdul Ghofar (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2024)
This study aims to analyze the effect of strategic leadership on organizational performance, with organizational ambidextrous as a mediating variable. The study used a quantitative approach and involved 90 Batik SMEs in Yogyakarta as samples. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results showed that leadership strategy had a positive and significant effect on organizational performance, which means that the leader's ability to manage long-term vision and innovation strategically contributes to improving organizational performance. In addition, leadership strategy was also found to have a positive and significant effect on organizational ambidextrous, which describes the organization's ability to manage resource exploration and exploitation simultaneously. These findings indicate that ambidextrous organizations also have a positive effect on organizational performance. Overall, ambidextrous organizations were shown to be able to mediate the effect of strategic leadership on organizational performance, indicating that the ability of strategic leaders to balance innovation and efficiency plays an important role in driving better performance. This study contributes to the literature on leadership strategy and organizational ambidextrous and offers insights for SME managers to improve performance through adaptive and innovative leadership.